2013
DOI: 10.1039/c3sm00135k
|View full text |Cite
|
Sign up to set email alerts
|

Swelling-induced deformations: a materials-defined transition from macroscale to microscale deformations

Abstract: Swelling-induced deformations are common in many biological and industrial environments, and the shapes and patterns that emerge can vary across many length scales. Here we present an experimental study of a transition between macroscopic structural bending and microscopic surface creasing in elastomeric beams swollen non-homogeneously with favorable . We show that this transition is dictated by the materials and geometry of the system, and we develop a simple scaling model based on competition between bending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
(53 reference statements)
1
36
0
Order By: Relevance
“…was studied; it was shown that wrinkling of the thin layer is an admissible deformation mode of the system, which did not bend due to the constraints of the substrate. A similar problem can also be found in [20], where bending of a homogeneous beam swollen by a solvent droplet put on the top surface is studied; it was shown that, at equilibrium, the beam recovers the straight initial configuration, whereas, during the transient, bending can only occur if the thickness of the beam is below the so-called elastoswelling length scale. Otherwise, wrinkling of the swollen top surface appears.…”
Section: (A) Asymptoticsmentioning
confidence: 92%
“…was studied; it was shown that wrinkling of the thin layer is an admissible deformation mode of the system, which did not bend due to the constraints of the substrate. A similar problem can also be found in [20], where bending of a homogeneous beam swollen by a solvent droplet put on the top surface is studied; it was shown that, at equilibrium, the beam recovers the straight initial configuration, whereas, during the transient, bending can only occur if the thickness of the beam is below the so-called elastoswelling length scale. Otherwise, wrinkling of the swollen top surface appears.…”
Section: (A) Asymptoticsmentioning
confidence: 92%
“…This example problem is modeled after the recent experiments of Yoon et al (2010) which are similar to the experiments of Holmes and co-workers (Holmes et al, 2011;Pandey and Holmes, 2013). In the experiments of Yoon et al (2010) a thin layer of a swellable gel is bonded to a non-swellable elastomer, the gel is allowed to swell and this causes large bending of the bilayer.…”
Section: Constrained Swelling Of a Bilayer In Plane Strainmentioning
confidence: 97%
“…For example, recently Giner et al (2009) published an ABAQUS implementation of the extended finite element method for linear elastic fracture analysis as a UEL subroutine. Also Park and Paulino (2012) published an ABAQUS implementation of a cohesive finite element as a UEL subroutine. In both cases, for educational purposes, the numerical implementation is discussed in detail, and the source code for the UEL was provided.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creases, however, have been observed routinely on elastic blocks compressed by various means, including mechanical forces Gent and Cho, 1999;Ghatak and Das, 2007;Mora et al, 2011), constrained swelling (Arifuzzaman et al, 2012;Barros et al, 2012;Dervaux and Ben Amar, 2012;Dervaux et al, 2011;Guvendiren et al, 2010;Ortiz et al, 2010;Pandey and Holmes, 2013;Tanaka, 1986;Tanaka et al, 1987;Trujillo et al, 2008;Weiss et al, 2013;Zalachas et al, 2013), temperature change , electric fields (Park et al, 2013;Wang et al, 2012;Wang et al, 2011;Wang and Zhao, 2013a;Xu and Hayward, 2013), and light (Yoon et al, 2012). Creases have been studied in soft tissues (Bayly et al, 2014;Jin et al, 2011;Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%